Studies on in vitro regeneration and biological activities of punica granatum l / Siti Zafirah Binti Azmi - Azmi, Siti Zafirah (2014)
The present study deals with tissue culture of Punica granatum L. Nodal stem explant was found to be the best explant which gave the highest shoot number (3.8±0.2) on MS medium supplemented with 1.5 g/L BAP, while shoot tip explant (1.9±0.1cm) on MS medium with 2.0 mg/L BAP gave the best shoot height. MS supplemented with 1.5 mg/L BAP was observed to give the highest shoot production (4.1±0.2) with combination of 40 g/L of sucrose in shoot tip explant. Complete plant regeneration was achieved for both shoot tips and nodal stem explants cultured on MS medium supplemented with 1.5 mg/L BAP. In scanning electron microscopy studies, in vitro leaf exhibited higher stomata density compared to in vivo leaf sample. No irregular characteristics were found in in vitro leaf and stem samples when compared to the in vivo leaf and stem samples. In callus production from P.granatum L., the highest callus weight was obtained from root explants cultured on MS supplemented with 1.5 mg/L BAP and 1.5 mg/L NAA (0.48±0.08g) and the highest callus weight using other auxins and cytokinins (IAA, IBA, 2,4-D and Kinetin) was obtained from stem explants supplemented with 2.0 mg/L IBA (0.26 ±0.01g). The highest percentage of radical scavenging activity was obtained from in vivo leaf extract with 67.4% at 100 μg/ml of sample concentration. Peel extract exhibited the highest percentage of radical scavenging activity of all samples (77.6%) and also the strongest IC50 value (2.21 mg/ml), at 100 μg/ml of sample concentration. Phytochemical contents that were presence in in vivo P.granatum L. sample were also presence in in vitro samples such as saponin, tannins, flavonoids and reducing sugar. Between peel and seed extracts of P.granatum L., terpenoid was detected but tannins and reducing sugars were detected only in peel extract.